Experimental Warming Has Not Affected the Changes in Soil Organic Carbon During the Growing Season in an Alpine Meadow Ecosystem on the Qinghai–Tibet Plateau - Yang, Yue; Shi, Guoxi; Liu, Yongjun; Ma, Li; Zhang, Zhonghua; Jiang, Shengjing; Pan, Jianbin; Zhang, Qi; Yao, Buqing; Zhou, Huakun; Feng, Huyuan (Frontiers in Plant Science, 2022)
The effects of climate warming and season on soil organic carbon (SOC) have received widespread attention, but how climate warming affects the seasonal changes of SOC remains unclear. Here, we established a gradient warming experiment to investigate plant attributes and soil physicochemical and microbial properties that were potentially associated with changes in SOC at the beginning (May) and end (August) of the growing season in an alpine meadow ecosystem on the Qinghai-Tibet Plateau. The SOC of August was lower than that of May, and the storage of SOC in August decreased by an average of 18.53 million grams of carbon per hectare. Warming not only failed to alter the content of SOC regardless of the season but also did not affect the change in SOC during the growing season. Among all the variables measured, microbial biomass carbon was highly coupled to the change in SOC. These findings indicate that alpine meadow soil is a source of carbon during the growing season, but climate warming has no significant impact on it. This study highlights that in the regulation of carbon source or pool in alpine meadow ecosystem, more attention should be paid to changes in SOC during the growing season, rather than climate warming.